Emergence of a novel reassortant H3N6 canine influenza virus - Meng, Bo; Li, Hailing; Feng, Chong; Guo, Weiwei; Feng, Yali; Zhu, Dawei; Chen, Hualan; Zhang, Ying (Frontiers in Microbiology, 2023)
Although the natural hosts of avian influenza viruses (AIVs) are wild birds, multiple subtypes of AIVs have established epidemics in numerous mammals due to their cross-species spillover. Replication and evolution in intermedia mammalian hosts may facilitate AIV adaptation in humans. Because of their large population and intimacy with humans, dogs could act as such an intermedia host. To monitor the epidemiology of canine influenza viruses (CIVs) in Liaoning, China, we performed three surveillances in November 2018, March 2019, and April 2019. Five H3N2 and seven novel H3N6 CIVs had been isolated. Since the N6 neuraminidase (NA) genes were clustered with the H5N6 AIV, there is a high possibility that these H3N6 CIVs were generated from a H3N2 CIVs and H5N6 AIVs reassortment case. In addition, the H3N6 CIV showed increased mammalian adaptation ability compared to all the H3N2 strains in both in vitro and in vivo studies. Even though isolated 3 months later, the March 2019 isolated H3N2 viruses replicated more efficiently than the November 2018 isolated viruses. Our study indicated that H3 CIVs were undergoing an evolution process, through both genetic mutations and gene reassortment, at an incredible speed.